Takotsubo's cardiomyopathy with an uncommon complication: implications for management and treatment. (January 2015) - Gibson, Robert; Chertoff, Jason
ABSTRACT : We present the case of a 57-year-old female with no significant history of cardiac disease admitted to our service with stress-induced cardiomyopathy (Takotsubo's cardiomyopathy). Admission echocardiography with contrast showed a non-mobile apical-filling defect, consistent with laminar thrombus. After 1 month of anticoagulation with warfarin (bridged with inpatient intravenous heparin), follow-up echocardiography with contrast showed resolution of the thrombus. Although reported in the literature, to our knowledge, there are no consensus guidelines for the surveillance and treatment of left ventricular thrombus in patients with Takotsubo's cardiomyopathy. An awareness of this adverse effect and its treatment implications is imperative for any clinician caring for these patients.